Справочник по блоку НАТО и вооружённым силам стран-членов НАТО: учебное пособие - Горев В. Д. Василий Дмитриевич; Поздняков Н. А. Николай Анатольевич; Голёнко Н. Е. Николай Ефимович; Кисляк А. А. Андрей Антонович (Томск, Изд-во ТПУ, 2017)
Заглавие с титульного экрана